FAKTOR-FAKTOR YANG MEMPENGARUHI OPINI AUDIT ATAS LAPORAN KEUANGAN PEMERINTAH DAERAH KOTA SE-INDONESIA - Harryansyah Putra; Anggeraini Oktarida; Yuli Antina Aryani; Dian Ofasari; Selvita Meilansari (Jurnal Riset Terapan Akuntansi, 2026)
This research aims to analyze the size of local governments in relation to audit opinions on the financial statements of local government cities in Indonesia, actions taken on audit recommendations, audit findings regarding non-compliance with laws and regulations, and weaknesses in internal control systems. This study is quantitative using secondary data from the Audit Results Reports of the BPK for the years 2021-2023. The research collected 279 samples from 93 cities across Indonesia. Data analysis was conducted using logistic regression with SPSS 26. The research results show that only the result of non-compliance with regulations has a partially negative impact on audit opinion. Meanwhile, the results regarding internal control weaknesses, recommended actions, and the size of local governments do not have a significant impact. However, all four variables have a simultaneous effect on audit opinion. Keywords: : Internal Control Findings, Legal Non-compliance, Audit Recommendation Follow-Up, Local Government Size, Audit Opinion.